Mechanisms and Efficacy of Chinese Herbal Medicines in Chronic Kidney Disease - Zhao, Mingming; Yu, Yi; Wang, Rumeng; Chang, Meiying; Ma, Sijia; Qu, Hua; Zhang, Yu (Frontiers in Pharmacology, 2021)
As the current treatment of chronic kidney disease (CKD) is limited, it is necessary to seek more effective and safer treatment methods, such as Chinese herbal medicine (CHMs). In order to clarify the modern theoretical basis and molecular mechanisms of CHMs, we reviewed the knowledge based on publications in peer-reviewed English-language journals, focusing on the anti-inflammatory, antioxidative, anti-apoptotic, autophagy-mediated and antifibrotic effects of CHMs commonly used in kidney disease. We also discussed recently published clinical trials and meta-analyses in this field. Based on recent studies regarding the mechanisms of kidney disease in vivo and in vitro, CHMs have anti-inflammatory, antioxidative, anti-apoptotic, autophagy-mediated, and antifibrotic effects. Several well-designed randomized controlled trials (RCTs) and meta-analyses demonstrated that the use of CHMs as an adjuvant to conventional medicines may benefit patients with CKD. Unknown active ingredients, low quality and small sample sizes of some clinical trials, and the safety of CHMs have restricted the development of CHMs. CHMs is a potential method in the treatment of CKD. Further study on the mechanism and well-conducted RCTs are urgently needed to evaluate the efficacy and safety of CHMs.